2019
DOI: 10.1007/s11156-019-00862-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ownership structure, sub-optimal cash holdings and investment inefficiency on dividend policy: evidence from Indonesia

Abstract: We investigate how a firm's decision to hold excessive cash or to overinvest could influence its dividend payout policy in Indonesia. Additionally, we examine the association between corporate ownership structure and cash dividends. Using a data set of Indonesian listed firms for the period from 1995 to 2014, we find that excessive cash holding (overinvestment) positively (negatively) affects a firm's likelihood of paying dividends. Also, we find that family, foreign, state and institutional ownership have sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 78 publications
(100 reference statements)
0
15
0
5
Order By: Relevance
“…5% or more share ownership by institutional company means that those institutional companies are the majority share owner (Bhojraj & Sengupta, 2003;Lin & Fu, 2017). Moreover, Moin et al (2019) showed that during the year of 1995-2014, the average percentage of institutional ownerships in Indonesia is relatively low. The smallest share ownership by institutional company is 0.37% and the largest one is 13%.…”
Section: Sample and Populationmentioning
confidence: 99%
“…5% or more share ownership by institutional company means that those institutional companies are the majority share owner (Bhojraj & Sengupta, 2003;Lin & Fu, 2017). Moreover, Moin et al (2019) showed that during the year of 1995-2014, the average percentage of institutional ownerships in Indonesia is relatively low. The smallest share ownership by institutional company is 0.37% and the largest one is 13%.…”
Section: Sample and Populationmentioning
confidence: 99%
“…Pada tingkat kepemilikan manajerial yang tinggi, manajer cenderung mengalokasikan laba untuk ditahan dibandingkan membayar dividen dengan alasan sumber dana internal lebih efisien dibandingkan sumber dana eksternal dalam pertumbuhan perusahaan. Penelitian yang dilakukan oleh Moin et al (2019) menunjukkan bahwa kepemilikan manajerial berpengaruh positif terhadap kecenderungan membayar dividen. Ditemukan inkonsistensi hasil penelitian yang diperoleh dari penelitian (Sari & Budiasih, 2016) yang menunjukkan bahwa kepemilikan manajerial berpengaruh negatif signifikan pada kebijakan dividen.…”
Section: Gambar 1 Dpr Perusahaanunclassified
“…Penelitian oleh Cheng et al (2018), Sindhu et al (2016), Jabeen dan Ahmad (2019) menemukan bahwa semakin stabil kepemilikan institusional, maka jumlah dividen yang dibagikan akan semakin besar pula. Ditemukan inkonsistensi hasil penelitian yang diperoleh dari penelitian Sari & Budiasih (2016), Al-Najjar & Kilincarslan (2016), Rajput & Jhunjhunwala (2019), dan Moin et al (2019) yang menunjukkan bahwa kepemilikan institusional menunjukkan berpengaruh negatif terhadap kebijakan dividen.…”
Section: Gambar 1 Dpr Perusahaanunclassified
See 1 more Smart Citation
“…Besides, good corporate governance could improve the company's value. Moin et al, (2019) added that corporate governance helps to measure a conflict of interest between controlling and minority shareholders through monitoring the manager.…”
Section: Agency Theorymentioning
confidence: 99%